The Effectiveness of Al-Ta'hil Al-Fiqhiy Method in Improving the Cognitive Ability of STIBA Makassar Students - Dahmayanti, Andi; Sirajuddin, Sirajuddin; Nur, Sri Reski Wahyuni (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
The objective of this study is to assess the efficacy of the Al-Ta’hῑl Al-Fiqhῑy learning approach in enhancing students' cognitive capabilities at STIBA Makassar. A true experiment with a posttest-only control group design was employed to assess the substantial impact of the method on students in their seventh semester. The findings of this study indicate that implementing the Al-Ta’hῑl Al-Fiqhῑy method markedly enhanced students' cognitive abilities. The calculated value of Cohen's d reached 1.26, indicating a huge effect size with a probability of 81.4% that the observed difference is due to the intervention and not other confounding factors. Moreover, the results of Cohen's U3 test demonstrated that 89.7% of students in the experimental group exhibited higher cognitive scores than those in the control group. These findings suggest that the Al-Ta’hῑl Al-Fiqhῑy method represents an effective alternative for enhancing the quality of education and fostering deeper comprehension in the field of fiqh. Keywords: Effectiveness, Al-Ta’hῑl Al-Fiqhῑy Method, Cognitive Ability.